2021
DOI: 10.1002/jrs.6195
|View full text |Cite
|
Sign up to set email alerts
|

Development of a gas‐phase Raman instrument using a hollow core anti‐resonant tubular fibre

Abstract: Versatile and flexible gas analysis for compositional identification and quantification is a demand found in a variety of diverse sectors. As such, a compact, deployable instrument exhibiting both high specificity and sensitivity is a highly attractive proposition for a wide range of applications. In this paper, we describe a gas phase Raman spectroscopy-based device using state-of-the-art anti-resonant (tubular) hollow core micro-structured optical fibre (HC-MOF).This fibre architecture allows the use of leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Because of this, t authors do not intend to provide a detailed analysis, but rather to provide a pathway readers to obtain more information. All three sensors have a commonality, which is th they have a comb-like, periodic structural variation in the refraction index within the fib core that induces a coupling action between the core mode and other modes support The second class of sensors in this category is classified as surface Raman spectroscopy (SRS), and there are a number of variants [49][50][51]. The underlying principle of operation is inelastic scattering of incident photons by the gas, some of which induce excitation of vibration states of gas molecules generating phonons and detectable energy dissipation.…”
Section: Optical Fibre Grating Sensorsmentioning
confidence: 99%
“…Because of this, t authors do not intend to provide a detailed analysis, but rather to provide a pathway readers to obtain more information. All three sensors have a commonality, which is th they have a comb-like, periodic structural variation in the refraction index within the fib core that induces a coupling action between the core mode and other modes support The second class of sensors in this category is classified as surface Raman spectroscopy (SRS), and there are a number of variants [49][50][51]. The underlying principle of operation is inelastic scattering of incident photons by the gas, some of which induce excitation of vibration states of gas molecules generating phonons and detectable energy dissipation.…”
Section: Optical Fibre Grating Sensorsmentioning
confidence: 99%
“…At present, several signal-enhancing devices have been proved to be effective: passively locked cavities, [1][2][3][4] where the work of Ohara et al showed a limit of detection (LOD) of 100 ppm for methane with 1-s exposure time and 40-W intra-cavity power, [2] and the work of Frosch et al showed a signal enhancement of 6 orders of magnitude [3] as well as LODs between 150 and 350 ppm in the process monitoring of biogas production [4] ; actively locked cavities, [5][6][7] where Hippler's work arrived a LOD of 1 mbar in 1 bar of total pressure (1000 ppm) with a diode laser of 10 mW and integration time of 30 s [5] ; multipass cells, [8][9][10] where the work of Velez et al recorded a LOD of methane below 1 ppm with a multi-mode diode laser of 6 W and exposure time of 5 s [10] ; functionalized waveguides, where the work of Holmstrom et al showed an enhancement over 9 orders of magnitude with a strong dependence on analytes [11] ; and hollowcore fibers (HCFs). [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Among these, HCF is an excellent component, which can be used not only as gas sample cells with long optical path but also as effective collectors of Raman radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development of microstructure fiber technology, many types of HCFs had been applied for fiber-enhanced Raman spectroscopy (FERS) of gaseous samples, such as metal-coated capillaries (MCCs), [13,14] hollow-core photonic bandgap fibers (HC-PBFs), [15][16][17][18][19] kagome HCFs, [20,21] and hollow-core anti-resonant fibers (HC-ARFs). [22][23][24][25] The advantage of MCCs is that the gas exchange rate is fast because of the large core diameter, but its enhancement of Raman scattering is not as good as other types of fiber. [12] In the previous studies, the best LOD of FERS system based on HC-PBF was reported as 0.2 ppm for methane (CH 4 ) with the excitation laser power of 2 W and the gas pressure of 20 bar, [15] and the best LOD of FERS system based on HC-ARF was reported as 3 ppm for CH 4 , 49 ppm for hydrogen (H 2 ) with the excitation laser power of 1.3 W and the gas pressure of 4 bar.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations